Common Complications in Endodontics Prevention and Management (Springer International Publishing, 2018)
This book describes the most commonly encountered endodontic complications and provides up-to-date information on their prevention and management. The opening chapters explain the importance of accurate diagnosis and treatment planning, outline the role of digital radiography and CBCT in managing complications, and highlight the need for close attention to anatomic landmarks in order to avoid damage to neurovascular anatomy. Endodontic problems associated with different procedural errors are then discussed in detail, covering a wide variety of access- and instrumentation-related complications and the difficulties that may arise when using obturation techniques. Readers will also find information on the endodontic-periodontal relationship, special issues in geriatric patients, and the potential medical emergencies and precautions in specific patient subsets. The clear, easy-to-read text is complemented by numerous high-quality photographs and tables that assist understanding and ready identification of management solutions. This book will be of value for all dental practitioners with an interest in endodontics, endodontic specialists, and higher-level students.